Da experiência da fala de sujeitos usuários na clínica psicológica às suas possíveis repercussões - Pereira, Lucyanna de Farias Fagundes (2006)
This work intends to promote a reflection about the psychological clinic and its repercussions as a place of opening to a creative speech of direction, starting from the experience of users. Understanding that it has a particularity of the language in the space of the psychological clinic, one believes that this work makes possible a better clarity as to the propriety, singularity and importance of speech in the clinic, besides taking the reflections and discussions about the thematic, as much to the academy as the fields of activity of the psychologist. The research restricts the clinic in its modality of psycotherapy, in order to reflect concerning the language in the narrative of the user. The listening of the experiences of clients who searched for psychotherapy assistance was induced by a triggering/provoking question, and the understanding of their narratives had as a support the existential phenomenological investigative methodology. The discussions became possible from affectations and reflections between testimonies and researcher, as well as from dialogues with authors who deal with the subject.